2002
DOI: 10.1023/a:1020890921238
|View full text |Cite
|
Sign up to set email alerts
|

Increased False Negative Rates in Sentinel Lymph Node Biopsies in Patients with Multi-Focal Breast Cancer

Abstract: There are few data about the reliability of sentinel node biopsy in patients with multi-focal breast cancer. The aim of this study was to determine the factors affecting the identification and accuracy of the sentinel node, comparing multifocality with other variables, using peritumoral isosulfan blue dye injection technique alone. Between 1998 and 2001, 122 patients with clinically negative nodes from a single institute were eligible for sentinel lymph node biopsies (SLNBs). All patients underwent conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 26 publications
2
19
2
2
Order By: Relevance
“…Therefore, accurate staging is necessary to determine the prognosis and the need for adjuvant therapy in patients [3,4]. Sentinel lymph node (SLN) biopsy has evolved as a technique for staging accurately the axilla with less morbidity than routine axillary lymph node dissection (ALND) in breast cancer [5][6][7][8][9][10][11][12][13][14]. Because the non-SLNs were found unlikely to be involved, if the SLNs are negative [15][16][17][18], completion, axillary dissections (CAD) are not routinely performed, and randomized trials are ongoing to validate omission of CADs in those patients [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurate staging is necessary to determine the prognosis and the need for adjuvant therapy in patients [3,4]. Sentinel lymph node (SLN) biopsy has evolved as a technique for staging accurately the axilla with less morbidity than routine axillary lymph node dissection (ALND) in breast cancer [5][6][7][8][9][10][11][12][13][14]. Because the non-SLNs were found unlikely to be involved, if the SLNs are negative [15][16][17][18], completion, axillary dissections (CAD) are not routinely performed, and randomized trials are ongoing to validate omission of CADs in those patients [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In view of these numbers, accurate staging seems particularly relevant in patients with multiple malignancies within one breast. Yet the reported false-negative rate of sentinel node biopsy is high [7,24,25]. Ozmen et al found a significant association between multicentric/multifocal disease and a false-negative procedure and Fearmonti et al particularly mention the risk of a falsenegative procedure in those with a large additive tumour burden [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Yet the reported false-negative rate of sentinel node biopsy is high [7,24,25]. Ozmen et al found a significant association between multicentric/multifocal disease and a false-negative procedure and Fearmonti et al particularly mention the risk of a falsenegative procedure in those with a large additive tumour burden [24,25]. A recent prospective multiinstitutional study by Giard et al showed a 13.6% false-negative rate of sentinel node biopsy after a single tracer injection in the breast [7].…”
Section: Discussionmentioning
confidence: 99%
“…Examples are previous surgery of the breast or axilla (Case 4), multicentricity [12][13][14], and extensive ductal carcinoma in situ. Ductal carcinoma in situ should not metastasize by definition, but in some 6% of these patients metastases are found in sentinel nodes.…”
Section: Discussionmentioning
confidence: 99%